2006
DOI: 10.1007/s10822-006-9080-0
|View full text |Cite
|
Sign up to set email alerts
|

QSAR analyses on avian influenza virus neuraminidase inhibitors using CoMFA, CoMSIA, and HQSAR

Abstract: The recent wide spreading of the H5N1 avian influenza virus (AIV) in Asia, Europe and Africa and its ability to cause fatal infections in human has raised serious concerns about a pending global flu pandemic. Neuraminidase (NA) inhibitors are currently the only option for treatment or prophylaxis in humans infected with this strain. However, drugs currently on the market often meet with rapidly emerging resistant mutants and only have limited application as inadequate supply of synthetic material. To dig out h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Scheme 1 lists several potent NA inhibitors, including zanamivir, oseltamivir carboxylate and BA. Note that oseltamivir is the prodrug of oseltamivir carboxylate (GS4071, compound 2).…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Scheme 1 lists several potent NA inhibitors, including zanamivir, oseltamivir carboxylate and BA. Note that oseltamivir is the prodrug of oseltamivir carboxylate (GS4071, compound 2).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the NA amino acids showed that these eight isolates have the 20-amino acid stalk deletion that is associated with adaptation of influenza viruses from aquatic birds to territory poultry [7–10]. These eight isolates do not possess any of the amino acids in the catalytic and framework sites that are responsible for resistance to NA-inhibitor drugs [1114]. Group A viruses did have a unique potential glycosylation site at amino acid position 50, which has also been observed in some H5N1 viruses isolated in China during 2001–2003, according to the sequence data in the influenza databases.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular structures of 48 NA inhibitors used in this study are listed in Table 1, which are collected from literatures. [41][42][43] Ten physicochemical properties are used in the FB-QSAR study. The codes and the physical implications of the 10 properties are listed in Table 2, including the charge descriptors, molecular shape descriptors, interaction descriptors, and solvation descriptors.…”
Section: Calculations and Resultsmentioning
confidence: 99%